Development of a Bilayer Tablet by Fused Deposition Modeling as a Sustained-Release Drug Delivery System - Andrea Gabriela Crișan; Alina Porfire; Sonia Iurian; Lucia Maria Rus; Raluca Lucăcel Ciceo; Alexandru Turza; Ioan Tomuță (MDPI AG, 2023)
Three-dimensional printing by fused deposition modeling (FDM) coupled with hot-melt extrusion (HME) is a point of convergence of research efforts directed toward the development of personalized dosage forms. In addition to the customization in terms of shapes, sizes, or delivered drug doses, the modulation of drug release profiles is crucial to ensure the superior efficacy and safety of modern 3D-printed medications compared to those of conventional ones. Our work aims to solidify the groundwork for the preparation of 3D-printed tablets that ensure the sustained release of diclofenac sodium. Specifically, we achieved the fast release of a diclofenac sodium dose to allow for the prompt onset of its pharmacological effect, further sustaining by the slow release of another dose to maintain the effect over a prolonged timeframe. In this regard, proper formulation and design strategies (a honeycomb structure for the immediate-release layer and a completely filled structure for the sustained-release layer) were applied. Secondarily, the potential of polyvinyl alcohol to function as a multifaceted polymeric matrix for both the immediate and slow-release layers was explored, with the objective of promoting the real-life applicability of the technique by downsizing the number of materials required to obtain versatile pharmaceutical products. The present study is a step forward in the translation of HME-FDM-3DP into a pharmaceutical manufacturing methodology.